Enhancing The Growth and Yield of Bush Sitao Using Bio-Stimulants in the Philippines - Dinero, Eugene Caesar H.; Frias, Jimlo C.; Sarona, Warren D.; Oñal, Paulino Miguel M.; Oñal, Jr., Paulino A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study aims to determine the effects of different levels of concentrations of bio-stimulant solution (BSS) in enhancing the growth and yield of bush sitao plant. The study was conducted at Bacolod City, Philippines. It was laid-out in RCBD (Randomized Complete Block Design) with 4 treatments, and replicated 4 times. Statistical analysis revealed a highly significant differences among treatments in growth parameters such as the flower initiation, plant height, weight of stems and leaves, and biomass from plants applied with 15% BSS (ɑlpha = 0.01). Furthermore, results indicated highly significant differences with yield parameters as well, namely the number of pods per plant, pod weight per plant, number of seeds per pod, total weight of 100-seeds, and the yield in kg/ha (ɑlpha = 0.01). The weight of stems and leaves and biomass accumulation were strongly correlated with the plant height while weight of roots were correlated moderately (ɑlpha = 0.01). Relatively, the number of pods per plant, pod weight, as well as the number of seeds per pods were strongly correlated with the yield. Based on excellent results of the study, for bush sitao it is recommended to apply BSS with a concentration of 15% in order to enhance the growth and yield of the plant. Furthermore the result could contribute to organic farming and food sustainability program being aspired in the whole world.